Analytical solution of the bond behavior of FRCM composites using a rigid-softening cohesive material law. (1st October 2019) - Calabrese, Angelo Savio; Colombi, Pierluigi; D'Antino, Tommaso
Abstract: The study of the bond behavior of fiber-reinforced composite materials applied to cohesive substrates is a fundamental topic to correctly understand the composite-substrate stress-transfer mechanism. Bond tests of fiber reinforced cementitious matrix (FRCM) composites comprising one layer of fiber textile generally showed failure due to debonding of the textile at the matrix-fiber interface. This failure mode was described considering a fracture mechanics pure Mode-II loading condition, which provided a bond differential equation that was solved once a certain shape of the interface cohesive material law was assumed. In this paper, a rigid-softening cohesive material law, which considers the possible presence of friction stress contributions at the debonding interface, is adopted to provide the analytical solution of the matrix-fiber interface full-range behavior in FRCM composites. The solution obtained is employed to reproduce the load responses of a PBO FRCM composite subjected to a recently-developed pull-out test and validate the analytical approach.